The relationship between pre-season workload indicators and changes in the yo-yo intermittent recovery test in professional soccer - Jasper, A.; Brink, M. S.; Frencken, W.; Helsen, W. F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Aim: In pre-season, a main objective is to develop aerobic fitness to prepare for the competitive season. Workload monitoring can aid in maximizing training adaptations. However, it remains unclear which workload indicators best relate to changes in fitness in professional soccer [1]. Therefore, the aim was to examine the association between workload indicators and changes in the Yo-Yo intermittent recovery test. Methods: During the first 2 weeks of pre-season, both external (total distance, distance covered in velocity zones (15-20 km/h, 20-25km/h and >25km/h) and PlayerLoadTM) and internal (sRPE multiplied by duration) training and match load were collected in 15 professional soccer players (mean age ± SD: 22,2 ± 3,6 years). A submaximal Yo-Yo intermittent recovery test level 1 (sYYIRT1; a duration of 8 minutes and 58 seconds, up to 8 repetitions at 15 km/h) was performed at baseline and 2 weeks thereafter. Cumulative workloads over 2 weeks as well as in the week preceding the second sYYIRT1 were related to relative changes in average heart rate over the last 60 second (HRex) of sYYIRT1. Pearson correlations were used to assess relations. Results: A significant lower average heart rate (p < 0.01) was observed during the second sYYIRT1 (167,9 ± 7,7 beats/min) compared to the first test (179,8 ± 8,2 beats/min). More distance covered in velocity zone 15-20 km/h in the week preceding the second sYYIRT1 was related to a negative percentage change in HRex (r = -0.64, p < 0.05). Other indicators were not significantly related to changes in HRex. Conclusion: Distance covered in velocity zone 15-20 km/h in the week preceding the second sYYIRT1 is related to improvements in fitness during pre-season. The Yo-Yo test performance is positively related to distance covered above 15 km/h in professional matches [2]. A similar type of workload (15-20 km/h) in turn appears to result in a beneficial stimulus for the physical capacity in intermittent exercise. Careful planning of distance covered in the 15-20km/h velocity zone should be considered to optimize training regimes during pre-season.